Futurability, Survivability, and the Non‐Steady State in the Intergenerational Sustainability Dilemma - Saijo, Tatsuyoshi (2024)
The three pillars of society—democracy, the market, and science and technology—are not systems that guarantee survival. This is because they will cause “future failures” that will eventually impose heavy burdens on future generations. Therefore, we need to design mechanisms to reinforce these three systems. This is called future design. Its basic concept is “futurability,” which is the ability of the current generation to prioritize the interests of future generations. This study examines the necessity of futurability, its background, and its relationship with intergenerational equity. In particular, using a simple numerical model in which the investment of the current generation affects the resources of future generations, this article shows that if each generation looks only to its own interests, humanity will face extinction. To ensure the survivability of humanity, each generation must demonstrate futurability, especially the importance of demonstrating futurability in a non-steady state.